(untitled) (International Journal of Innovative Technologies in Economy, 2023)
Keeping the population in the mountainous regions and their social and economic development is one of the significant challenges of modern times. Therefore sustainable development of highlands highly depends on the rational usage of local natural resources. In this line, the priority is given to touristic-recreational resources in the mountainous Ajara, which are not completely assimilated yet. Touristic-recreational resources of mountain-climatic resort Beshumi and the properties of its application for touristic purposes are studied in the work via the application of traditional and modern methods. The development level of the tourism industry and originalities of tourists` dynamics are established. Potential of tourists` transmittance is evaluated and the challenges existed towards the resort are determined. Local population`s attitude towards the tourism is found out, an in line with fields of regional economy - tourism priorities are evaluated and its further development perspectives are set.